Addressing Learning Barriers and Needs in Scientific Writing: A Study of Indonesian Language and Literature Education Students - Nurfathana Mazhud; Nurmiah Muin (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study investigates the learning barriers and needs of Indonesian Language and Literature Education (PBSI) students at the Faculty of Letters, Muslim University of Indonesia (UMI), in the context of writing scientific papers, proposals, and theses. Adopting a descriptive qualitative approach supplemented by quantitative questionnaire data, the research gathered insights through structured questionnaires, informal interviews, and classroom observations. The findings indicate that students encounter multifaceted challenges stemming from both internal factors such as low motivation, limited academic writing exposure, and self-efficacy concerns and external factors, including constrained time due to family and work responsibilities, a lack of standardized thesis guidelines, and minimal mentoring support. Despite recognizing the importance of robust academic writing skills, students frequently struggle with topic selection, constructing cohesive frameworks, and selecting appropriate research methods. These obstacles underscore the need for more practice-oriented instruction, continuous feedback loops, and comprehensive institutional support mechanisms. Recommendations include incorporating structured mentorship programs, providing faculty-wide writing manuals, and introducing iterative writing exercises within the Scientific Paper Writing Technique (TPKI) course. The implications of this study are threefold. Theoretically, it contributes to ongoing discourse regarding needs-based pedagogy in academic writing. Practically, it offers a roadmap for instructors, administrators, and policymakers to design targeted interventions that enhance student writing proficiency. Policy-wise, the findings stress the significance of establishing writing centers and standardized guidebooks to ensure consistent quality and compliance with academic standards. While the sample was confined to mid- and final-year PBSI students, future research could expand the scope by examining longitudinal progress in writing competencies or comparing outcomes across different disciplines and institutions. Overall, this study emphasizes the centrality of well-structured, context-specific support systems in cultivating effective scientific writing skills and advancing the scholarly contributions of undergraduate students.